Universal Basic Income versus Unemployment Insurance - Alice Fabre; Stéphane Pallage; Christian Zimmermann (Institute for the Study of Labor (IZA), 2014)
In this paper we compare the welfare effects of unemployment insurance (UI) with a universal basic income (UBI) system in an economy with idiosyncratic shocks to employment. Both policies provide a safety net in the face of idiosyncratic shocks. While the unemployment insurance program should do a better job at protecting the unemployed, it suffers from moral hazard and substantial monitoring costs, which may threaten its usefulness. The universal basic income, which is simpler to manage and immune to moral hazard, may represent an interesting alternative in this context. We work within a dynamic equilibrium model with savings calibrated to the United States for 1990 and 2011, and provide results that show that UI beats UBI for insurance purposes because it is better targeted towards those in need.
Keywords: E24; D7; J65; 330; universal basic income; idiosyncratic shocks; unemployment insurance; heterogeneous agents; moral hazard